Storytelling as A Humanistic Approach in Children Language Stimulation - Muryanti, Elise (Universitas Negeri Padang, 2020)
This article discusses the implementation of the storytelling method as humanistic learning in Finland Kindergartens. Language is one aspect of development that is stimulated at an early age. Humanistic learning is learning that optimizes the potential of children as humans. One of the practices of humanistic learning is using storytelling in teaching children. Through storytelling activities, children fulfill their basic needs in self-actualization. In the learning activities seen children in Finland are actively involved in storytelling and the teacher facilitates learning in accordance with the interests and children’s needs.Keywords: Storytelling, Humanistic Approach, Stimulation in Language Development